THU0083 The relevance of elevated crp as an inclusion criterion in clinical trials in patients with rheumatoid arthritis. (15th June 2017) - Scoville, C; Suboticki, J; Zhong, S; Keystone, E
Abstract : Background: Elevated C-reactive protein (CRP) is often used as an entry criterion in clinical trials (CT) of patients (pts) with rheumatoid arthritis (RA), resulting in the potential exclusion of pts with active disease and high screen failure rates 1 . Objectives: To assess the relevance of requiring an elevated CRP (≥1 mg/dL) as an inclusion criterion for clinical, functional, and radiographic outcomes. Methods: This post hoc analysis used data from 2 randomized CTs in RA pts with an inadequate response to methotrexate (MTX). In DE019, pts on background MTX received adalimumab (ADA) or placebo (PBO) 2 ; in MUSICA, pts received either 7.5 or 20 mg MTX, along with ADA 3 . Data from MUSICA were used to confirm observations from DE019. Pts were subgrouped by CRP level at entry (CRP <1 mg/dL, ≥1 mg/dL). Baseline (BL) demographics and disease characteristics were summarized for each group. Clinical efficacy was assessed through swollen/tender joint count (S/TJC) at 66/68 joints, pain, patient global assessment (PtGA), physician global assessment (PhGA), CRP, clinical disease activity index (CDAI), 28-joint disease activity score based on CRP (DAS28-CRP), and proportions of pts achieving ACR20/50/70. Functional outcomes were assessed by the disability index of the health assessment questionnaire (HAQ-DI), and radiographic outcomes by the modified total Sharp score (mTSS). Outcomes were assessed in pts with CRP <0.8 mg/dL in DE019, which included pts with CRP levels as low as 0.75 mg/dL Observed data are reported at week 24. Results: In DE019, 183 pts (89 and 94 in the ADA and PBO arms, respectively) had CRP <1 mg/dL and 224 pts (118 and 106, respectively) had CRP ≥1mg/dL. Pts with elevated CRP had higher BL disease activity compared with those with CRP <1 mg/dL at entry (not shown). After 24 wks of treatment with ADA, pts in both CRP subgroups experienced significant improvements in most clinical and functional outcomes vs PBO (Table). In pts with CRP <0.8 mg/dL, the ACR20 response rate difference (30.4, p<.001) and the difference in ΔmTSS (-1.3, p<.05) for ADA vs PBO treatment were still significant. Compared to pts with CRP <1 mg/dL, pts with elevated CRP experienced greater clinical and functional improvements. However, within the ADA subgroups, pts with elevated CRP had smaller differences vs PBO in mTSS, perhaps reflecting higher joint damage at BL. In general, similar trends were observed in MUSICA (not shown). Conclusions: While pts with elevated CRP at entry experienced larger improvements from BL in clinical and functional outcomes upon treatment, significant improvements in most outcomes were also observed in those without elevated CRP at entry (as low as 0.75 mg/dL), suggesting that an elevated CRP may not be required to see differences between active and inactive treatment. References: Von Vollenhoven et al. 2015, Arthritis Rheum 67: 2855–2860. Keystone et al. 2004. Arthritis Rheum;5:1400–11. Kaeley et al. 2016. J Rheum;8:1480–9. Acknowledgements: AbbVie: study sponsor, contributed to study design, data collection, analysis and interpretation; writing, reviewing, and approval of the final version. Medical writing assistance: Naina Barretto, of AbbVie. Disclosure of Interest: C. Scoville Speakers bureau: AbbVie, J. Suboticki Employee of: AbbVie, S. Zhong Employee of: AbbVie, E. Keystone Grant/research support from: AbbVie, Amgen, AstraZeneca, Biotest, Bristol-Myers Squibb, Centocor, F Hoffmann-LaRoche, Genentech, Genzyme, Merck, Novartis, Nycomed, Pfizer, and UCB., Consultant for: AbbVie, Amgen, AstraZeneca, Biotest, Bristol-Myers Squibb, Centocor, F Hoffmann-LaRoche, Genentech, Genzyme, Merck, Novartis, Nycomed, Pfizer, and UCB., Speakers bureau: AbbVie, Amgen, AstraZeneca, Biotest, Bristol-Myers Squibb, Centocor, F Hoffmann-LaRoche, Genentech, Genzyme, Merck, Novartis, Nycomed, Pfizer, and UCB.